(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2025)
The primary aim of our research was to study whether and how the position of the English interdental fricatives [θ] and [ð] in a word (initial, medial or final) affects the accuracy of their pronunciation, both in the individual word and textual context. We also studied which sounds were used as substitutions for [θ] and [ð] in the cases of inaccurate pronunciation. Moreover, we performed a comparative analysis between two age groups of primary school ESL students in order to evaluate a possible impact of training and language exposure on the production of English interdental fricatives. The obtained results show that the participants in our study most accurately pronounce the [θ] and [ð] sounds when they are placed in the final word position, with the voiceless interdental fricative [θ] being pronounced more accurately than its voiced pair [ð]. The [θ] and [ð] sounds were mostly substituted with the Serbian stops [t] and [d] , arguably due to the universal grammar constraints. The 8th graders showed greater accuracy in pronunciation of the [θ] and [ð] sounds in comparison to the 5th graders, which suggests the possibly postitive effect of training and language exposure on the production accuracy of the aforementioned sounds.